Peran Minat Beli dalam Memediasi Pengaruh Media Sosial, Electronic Word of Mouth, dan Citra Merek Terhadap Keputusan Pembelian Ramen Ramie - Fadhilah, Digan Zahroh; Silaningsih, Endang; Yuningsih, Erni (LPPM Institut Pendidikan Nusantara Global, 2025)
The development of the Food and Beverage (F&B) industry continues to increase. This increase is an opportunity for various business actors, one of which is Ramen Ramie Kemanggisan. However, consumer purchasing decisions for Ramen Ramie have decreased, allegedly due to the lack of utilization of marketing media. This study tested social media, eWOM, brand image, and purchase interest both simultaneously and partially on consumer purchasing decisions. The sampling technique used a non-probability sampling technique with a purposive sampling method. The research sample was 100 respondents using the Lemeshow formula. The data analysis technique used was descriptive verification analysis, validity and reliability tests, path analysis, and classical assumption tests. The results of the study showed that both simultaneously and partially there was a positive and significant influence of social media, electronic word of mouth (eWOM), and purchase intention on purchasing decisions. However, brand image did not have a simultaneous and partial effect on purchasing decisions. The implications of this study are to enrich empirical evidence related to the role of purchase intention in mediating social media, electronic word of mouth (eWOM), brand image on purchasing decisions of Ramen Ramie, and can be used as material for improvement for the company.